Successful Treatment of Linear Psoriasis With the IL-17a-Antagonist Ixekizumab: A Case Report - Christov S; Ohm F; Augustin M; Wagner JN (Psoriasis: Targets and Therapy)
Slatina Christov, Frenz Ohm, Matthias Augustin, Jan Nicolai Wagner Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), 20246 Hamburg, GermanyCorrespondence: Jan Nicolai Wagner, Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), 20246 Hamburg, Germany, Tel +49 (0) 40 74 10 52398, Fax +49 (0) 40 7410 55348, Email ja.wagner@uke.deAbstract: Linear psoriasis (LP) represents a rare variant of psoriasis. The clinical presentation includes erythematous plaques distributed along the Blaschko lines, reflecting the presence of embryological mosaicism. The clinical and histopathological features of this condition show many similarities with inflammatory linear verrucous epidermal nevus (ILVEN), which presents a challenge in differential diagnosis. Currently there is no disease-specific treatment guidelines causing a challenge in the therapeutic management. In this case report we describe a 28-year-old patient with LP. Clinically characterized by persistent, psoriasiform lesions that proved refractory to treatment with topical corticosteroids, vitamin D analogs, and systemic dimethyl fumarate. The histopathological findings showed psoriasiform epidermal hyperplasia with alternating ortho- and parakeratosis, subepidermal capillary dilatation, and perivascular lymphocytic infiltrates, confirming the diagnosis. Ixekizumab, a IL-17A antagonist, was administered leading to a rapid and significant reduction in disease severity within the first 16 weeks. The Psoriasis Area and Severity Index (PASI) decreased from 12.5 to 1.0 and as well as the Dermatology Life Quality Index (DLQI) improved to 1. Both scores prove significant improvement in quality of life and clinical severity. This case report shows the importance of histological confirmation in differentiating LP from clinically similar appearing diseases like ILVEN and highlights the potential therapeutic benefit of IL-17 blockade in LP. In addition, the findings emphasize the need for systematic studies to develop evidence-based treatment strategies for this rare psoriasis phenotype.Keywords: psoriasis, linear psoriasis, biologics, genodermatosis, ILVEN, IL-17A-antagonist, ixekizumab